Analisis Perbandingan Proses Pengajuan Izin Usaha Di Indonesia Dan Thailand: Tinjauan Terhadap Faktor-Faktor Penghambat Dan Solusinya - Halawa, Yubileum; Dompak, Timbul; Khairina, Etika (Prosiding, 2024)
This research compares the process of applying for business permits in Indonesia and Thailand and the inhibiting factors. Thailand has a more efficient process because it implements an online licensing system, while Indonesia still faces challenges such as regulatory complexity, lack of coordination, corrupt practices and limited human resources. Potential solutions include simplifying regulations, increasing coordination, eradicating corruption, increasing human resource capacity, and outreach to business actors. The role of information technology is crucial in this improvement process. It is hoped that this research will provide useful insights and recommendations for the government and stakeholders.